Implementasi Sistem Penagihan Piutang Jasa Body Repair Pada PT. Setiajaya Toyota Body And Paint Depok - Prayoga, Rizky; Muktiadji, Nusa; Roup, Abdul; Iriyadi, Iriyadi (Jurnal Aplikasi Bisnis Kesatuan, 2024)
The sale of body repair services is an effort to restore the condition and function of a vehicle damaged by the use of the vehicle to its original condition. The provision of body repair services can be done on credit, by the customer making a claim for damage to the vehicle to the insurance company, then the customer makes an advance payment, then the payment will be made by the insurance company in several installments or paid at once at maturity according to the total customer claim. Directly the sale of service services on credit will generate an account receivable. The purpose of the discussion of this final project is to find out how the sale of vehicle body repair services, which involves what documents are used for billing to the insurance, functions and procedures for providing body repair services and collecting receivables from body repair services. The results of the discussion show that the system for selling vehicle body repair services on credit at PT Setiajaya Toyota Body & Paint has been carried out quite well, it can be seen from its functions such as sales, warehouse, shipping, and billing functions for the sale of vehicle body repair services on credit. Documents used for billing to insurance are Work Order (SPK), Work Order (WO), Supply Slip (SS), Receipt, Tax Invoice, Epoxy Photo, and Document Receipt. Sales procedures for body repair services and also billing for body repair services that are applied are in accordance with the SOP of the company.   Keywords: System, Sales of Body Repair Services